Cash reserve and venture business survival probability - Sheen Liu; Peter Woodlock; Howard Qi; Yan Alice Xie (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
Both solid business ventures and those not on as firm a footing can fail because they do not manage risk properly. This study shows that start-ups with a positive NPV project can fail because of inadequate cash reserves. We apply the first-hitting time model to analyze the effect of a cash reserve on the business failure density function and the cumulative failure probability for a specific business venture. The analysis of this model shows that business ventures have a much higher survival probability when they reduce their future cash-flow volatility. It is also shown that when risks cannot be controlled or are too expensive to be controlled, then business ventures need to have adequate cash reserves if they are to reduce failure density and cumulative failure probability.
Keywords: 650